Evaluation of Manual and Automated Bloodstream Infection Surveillance in Outpatient Dialysis Centers. (14th January 2016) - Thompson, Nicola D.; Wise, Matthew; Belflower, Ruth; Kanago, Meredith; Kainer, Marion A.; Lovell, Chris; Patel, Priti R.
Abstract : Outpatient hemodialysis bloodstream infection rates, now used for performance measurement and were significantly higher for manual compared with automated surveillance ( P <.001), largely owing to the absence of blood culture data in the dialysis electronic health record. Improvement in data sharing between hospitals and outpatient dialysis centers is necessary. Infect. Control Hosp. Epidemiol. 2016;37(4):472–474